GRIEF AND AFFECTION IN JOHN MICHAEL GREEN’S THE FAULT IN OUR STARS - Linus Rumapea; Alan Fernando (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The research is about grief and affection in John Michael Green’s The Fault in Our Stars. The novel is seen as the representation of people who undergo grief but can cope with by getting affection from others. This is a library research and applies mimetic theory proposed by Abrams saying that it is the explanation of art as essentially an imitation of aspects of the universe. However, literature as an art does not merely imitates the universe but it creates a new world that is taken from the real world. It means the story is reflects a real life through the literary work. The analysis is focused on grief and affection which represented by the characters Hazel Grace Lancaster, Augustus Waters, Isaac, Hazel’s parents and Augustus’ parents where they live their days with the fear of death, pain, and oblivion yet they try to figure out how to overcome their fear through affect each other. In conclusion, John Michael Green in his novel vividly portrays grief and affection.